Baseline type 2 biomarker levels and response to tezepelumab in severe asthma. Issue 6 (9th February 2022) - Corren, Jonathan; Pham, Tuyet‐Hang; Garcia Gil, Esther; Sałapa, Kinga; Ren, Pin; Parnes, Jane R.; Colice, Gene; Griffiths, Janet M.
Abstract: Background: Tezepelumab is a human monoclonal antibody that blocks activity of thymic stromal lymphopoietin (TSLP). In the phase IIb PATHWAY study (NCT02054130), tezepelumab significantly reduced annualized asthma exacerbation rates (AAERs) versus placebo in adults with severe, uncontrolled asthma. We evaluated the effects of tezepelumab in reducing type 2 (T2) inflammatory biomarker levels in the PATHWAY population, and the relationship between baseline T2 biomarker levels and AAER. Methods: Adults with severe, uncontrolled asthma ( n = 550) were randomized to tezepelumab (70 mg or 210 mg every 4 weeks, or 280 mg every 2 weeks) or placebo for 52 weeks. Blood eosinophil count, fractional exhaled nitric oxide (FeNO), and serum total immunoglobulin (Ig)E, interleukin (IL)‐5, IL‐13, periostin, thymus and activation‐regulated chemokine (TARC), and TSLP were measured at baseline and over 52 weeks. AAERs were analyzed by baseline threshold (high/low) biomarker levels. Results: Positive correlations were observed between T2 inflammatory biomarkers (blood eosinophil count, FeNO, IL‐5, IL‐13 and periostin) at baseline. At Week 52, treatment with tezepelumab 210 mg reduced all biomarker levels measured from baseline versus placebo. Exacerbations were reduced by 55–83% in the pooled tezepelumab cohort versus placebo, irrespective of baseline blood eosinophil count, FeNO, or serum total IgE, IL‐5, IL‐13, periostin, TARC, or TSLP, when these biomarkers were assessed individually. Conclusion: At baseline, positive correlations between specific T2 inflammatory biomarkers were observed. Tezepelumab reduced multiple T2 inflammatory biomarkers, which indicates decreased airway inflammation, and reduced exacerbations irrespective of baseline T2 biomarker profiles in patients with severe asthma. Abstract : This phase IIb, randomized, double‐blind, placebo‐controlled clinical trial evaluates the effects of tezepelumab in reducing type 2 inflammatory biomarkers and the relationship between baseline biomarker levels and annualized asthma exacerbation rates. Exacerbations are reduced by 55–83% in the pooled tezepelumab cohort compared to placebo, irrespective of baseline type 2 biomarker levels. At Week 52, treatment with tezepelumab reduces the levels of all measured biomarkers.Abbreviations: FeNO, fractional exhaled nitric oxide; IgE, immunoglobulin E; IL, interleukin; TARC, thymus and activation‐regulated chemokine; TSLP, thymic stromal lymphopoietin